NOVEL DRUG DELIVERY SYSTEMS: DESIRED FEAT FOR TUBERCULOSIS - Kirtipal Kaur; Anuj Gupta; R.K. Narang; R.S.R. Murthy (Wolters Kluwer Medknow Publications, 2010)
Tuberculosis has claimed its victims throughout much of known human history and is currently the most devastating human bacterial disease. The ability to infect human population on a global scale, combined with the widespread emergence of multi-drug resistant strains, has led to the placement of Mycobacterium tuberculosis on the National Institute of Allergy and Infectious Diseases (NIAID) list of Biodefence and Emerging Infectious Disease Threats Agents. The resurgence of interest in tuberculosis (TB) has stemmed because of increased evidences from developed countries. Contrary to expectations, no country has reached the phase of elimination and in no subsection of society TB has been completely eliminated. A deeper understanding of the process will assist in the identification of the host and mycobacterial efforts involved and provide targets for therapeutic strategies against tuberculosis. The article presents a view on pathogenesis of tuberculosis and its diverse manifestations, host defense evasion, mechanisms of microbial persistence, emergence of Multiple Drug Resistance and Extensive Drug Resistance, conventional therapy used and the possible novel systems which are under extensive investigation as drug carriers for improving the cytosolic concentration of the anti-tubercular agents.